Pengaruh Esg Performance, Financial Distress, dan Good Corporate Governance Terhadap Tax Avoidance - Mutiara Salsabila Hanifia,; Hexana Sri Lastanti, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to examine the influence of ESG performance, financial distress and good corporate governance on tax avoidance. The population of this research is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period. This research sample was taken using a purposive sampling method. Based on the criteria, the observation data found amounted to 82 data. Data were analyzed using multiple linear regression methods tested with SPSS 30. This research succeeded in finding that ESG performance has a negative effect on tax avoidance, financial distress have a positive effect on tax avoidance, and institutional ownership and independent commissioners have no effect on tax avoidance.